Expression of APP, CDK5, and AKT1 Gene Related to Alzheimer Disease in Brain of Long-tailed Macaques - Lis Rosmanah; Uus Saepuloh; Sela Septima Mariya; Irma Herawati Suparto; Wasmen Manalu; Adi Winarto; Huda Shalahudin Darusman (HAYATI Journal of Biosciences, 2024)
Amyloid plaques and Neurofibrillary Tangles (NFTs) are known to be key pathological features of Alzheimer disease. To gain a better understanding of this disease, studies were carried out on the Indonesian primates, the long-tailed macaques, using a spontaneous Alzheimer's disease model. Examining and identifying genetic markers involved in plaque formation and NFTs in long-tailed macaques is necessary to reveal their physiological processes. In this study, the expression of genes involved in the development of amyloid plaque (Amyloid Precursor Protein (APP)) and those that control the phosphorylation of tau protein (CDK5 and AKT1) was examined in the long-tailed macaque brain. This study showed that APP, CDK5, and AKT1 may potentially be developed as genetic markers of Alzheimer's disease. Long-tailed macaques exhibited the development of amyloid plaque in the aging brain based on the analysis of the gene expression profile of its biomarker. Furthermore, long-tailed macaques can be optimized for neurodegenerative models.